Expanding the Scope of Polymerization‐Induced Self‐Assembly: Recent Advances and New Horizons - Cao, Junpeng; Tan, Yingxin; Chen, Ying; Zhang, Li; Tan, Jianbo (Macromolecular rapid communications., 2021)
Over the past decade or so, polymerization‐induced self‐assembly (PISA) has become a versatile method for rational preparation of concentrated block copolymer nanoparticles with a diverse set of morphologies. Much of the PISA literature has focused on the preparation of well‐defined linear block copolymers by using linear macromolecular chain transfer agents (macro‐CTAs) with high chain transfer constants. In this review, a recent process is highlighted from an unusual angle that has expanded the scope of PISA including i) synthesis of block copolymers with nonlinear architectures (e.g., star block copolymer, branched block copolymer) by PISA, ii) in situ synthesis of blends of polymers by PISA, and iii) utilization of macro‐CTAs with low chain transfer constants in PISA. By highlighting these important examples, new insights into the research of PISA and future impact these methods will have on polymer and colloid synthesis are provided. Different from traditional polymerization‐induced self‐assembly (PISA) that focuses on the preparation of linear block copolymer nano‐objects using macromolecular chain transfer agents with high chain transfer constants, this review summarizes recent advances of PISA, which focuses on in situ synthesis of nonlinear architectures, blends of polymers, and utilization of poor polymerization control.